Optimization of squeeze casting parameters of hybrid aluminium matrix composite using Taguchi approach. (August 2021) - Arulraj, M; Palani, PK; Sowrirajan, M
Squeeze casting is one of the simplest processes of manufacturing of composite materials and it attains higher advantages of low material processing cost, easy handling of material, size, design and good stability of matrix structure. LM24 aluminium alloy reinforced with silicon carbide (SiC) and coconut shell ash (CSA) were used to prepare the composite. LM24 alloy had wide engineering applications, wherein the addition of SiC enhances the wear resistance and CSA particles offer significant technical and economic benefits. In the present study, the composite samples were prepared based on Taguchi experimental conditions L16 (4-levels and 5- parameters) through squeeze casting method. From the experimental results, percentage of reinforcement and squeeze pressure were most influential parameters on impact strength. The optimum casting condition was obtained by using Taguchi optimization. From microstructural study, applying high level of squeeze pressure improved the uniform dispersion, good bonding between the matrix and reinforcement. Also, 25% of impact strength was improved the composite using Taguchi optimum conditions compared than conventional alloys. Higher squeeze pressure seen to have refined dendritic structure with uniform distribution of reinforcement materials in the aluminium matrix.